PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DAN DAMPAKNYA TERHADAP LOYALITAS KARYAWAN (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2019)
The research aims to analyze empirical evidence of the influence of leadership style on employee performance and its impact on employee loyalty on PT. Fastrata Buana Branch Pulogadung. Samples obtained by 187 respondents, sample retrieval techniques using purposive sampling, namely sample retrieval techniques that provide equal opportunities for each element (member) of the population to be selected to be a sample member. Data collection techniques using questionnaires, data analysis techniques used are validity and reliability. The results of this study show that there is a positive and significant influence between leadership styles and on employee performance, leadership styles have positive and significant influence on employee loyalty, employee performance has positive and significant influence on employee loyalty, as well as a positive and significant influence between leadership styles on employee loyalty through employee performance